2022
DOI: 10.3390/cells11213513
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Antipsychotic Lurasidone Affects Brain but Not Liver Cytochrome P450 2D (CYP2D) Activity. A Comparison with Other Novel Neuroleptics and Significance for Drug Treatment of Schizophrenia

Abstract: The aim of this work was to study the effect of prolonged lurasidone administration on the cytochrome 2D (CYP2D) expression and activity in the rat liver and selected brain structures involved in the therapeutic or side effects of this neuroleptic. Male Wistar rats received lurasidone (1 mg/kg ip.) for two weeks. The activity of CYP2D was measured in brain and liver microsomes as the rate of bufuralol 1′-hydroxylation. The CYP2D protein level was determined in microsomes by Western blot analysis. The CYP2D gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, detail mechanisms by which drugs affect CYP2D protein levels in the brain have not been recognized so far. Our recent studies indicated similar effects of three atypical neuroleptics, asenapine, iloperidone and lurasidone, acting mainly as antagonists of dopaminergic D2 receptors and serotonergic 5-HT2/6/7 receptors, which affected the CYP2D activity/protein level in different brain regions (e.g., both drugs evoked a decrease in the frontal cortex and cerebellum, but increased it in the striatum) [ 27 , 38 , 39 ]. The changes produced by these three neuroleptics in brain CYP2D were different from and usually opposite to those found in the present work for the potential antidepressant CP-101,606.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, detail mechanisms by which drugs affect CYP2D protein levels in the brain have not been recognized so far. Our recent studies indicated similar effects of three atypical neuroleptics, asenapine, iloperidone and lurasidone, acting mainly as antagonists of dopaminergic D2 receptors and serotonergic 5-HT2/6/7 receptors, which affected the CYP2D activity/protein level in different brain regions (e.g., both drugs evoked a decrease in the frontal cortex and cerebellum, but increased it in the striatum) [ 27 , 38 , 39 ]. The changes produced by these three neuroleptics in brain CYP2D were different from and usually opposite to those found in the present work for the potential antidepressant CP-101,606.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that prolonged administration of some antidepressant and neuroleptic drugs affects CYP2D activity in brain structures involved in depression and schizophrenia (respectively), and influences the therapeutic action or side effects of those drugs (reviewed by [ 3 ]). Since CYP2Ds are engaged in the metabolism of endogenous neuroactive substances in the brain, changes in their activity may modify the pharmacological action of psychotropics, as recently suggested for the investigated antidepressants (e.g., escitalopram, venlafaxine) and atypical neuroleptics (e.g., asenapine, iloperidone and lurasidone) [ 15 , 27 , 37 , 38 , 39 ]. The abovementioned three atypical neuroleptics evoked similar pattern of changes in the regional CYP2D activity in the brain, which was different from that of antidepressants, and suggested the involvement of pharmacological (receptor) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it may be expected that in the human brain, CYP2D6 has a beneficial effect on the physiological level of active indoleamines, such as serotonin, melatonin and 5-methoxytryptamine. The role of CYP2D6 in the brain may be significant when the classical route of serotonin synthesis governed by tryptophan hydroxylase 2 (TPH2) is impaired [ 50 , 51 ] and/or when the CYP2D gene is duplicated or amplified ( CYP2D6*2 gene variant) or when CYP2D activity is modified by such inducers as alcohol or nicotine [ 43 , 52 , 53 , 54 , 55 ] or by psychotropic drugs, such as antidepressants [ 56 , 57 , 58 , 59 , 60 ] or neuroleptics [ 56 , 61 , 62 , 63 , 64 ]. The brain serotoninergic system has been shown to be involved in the pathophysiology of psychiatric disorders (depression, anxiety, schizophrenia) as well as in the mechanism of action of psychotropics, including antidepressants, anxiolytics or antipsychotics, respectively.…”
Section: The Contribution Of Cytochrome P450 To the Synthesis Of Sero...mentioning
confidence: 99%